AN ANALYTICAL STUDY ON THE HOLY QURAN BASED ON THE ORDER OF WORDS IN ARABIC AND CONJUNCTION - Bentrcia, Rahima; Zidat, Samir; Marir, Farhi (Malaysian Journal of Computer Science, 2018)
Some aspects of word relations are inspired from patterns of word co-occurrences. From this point, we conduct an analytical study on one type of these patterns, which is the AND conjunctive phrases, that exist in the holy Quran. First, we propose a set of AND conjunctive patterns in order to extract the conjunctive phrases from the Quranic Arabic Corpus, which we convert to Arabic script. Then, we analyze the order of the two words that form the conjunctive phrase. We report three different cases: words that have occurred in a specific order in the conjunctive phrase and repeated only once in the Quran, words that have occurred in a specific order in the conjunctive phrase and repeated many times in the Quran, and words that have occurred in two different orders in the conjunctive phrase and repeated one/many time(s) in the holy Quran. Finally, we show that different word orders in the conjunctive phrase yield different contextual meanings and association values between the combined words.